2014
DOI: 10.1007/s10072-014-1725-5
|View full text |Cite
|
Sign up to set email alerts
|

Hesperidin attenuates oxidative and neuronal damage caused by global cerebral ischemia/reperfusion in a C57BL/J6 mouse model

Abstract: The aim of this study was to determine the effects of hesperidin (HP) on neuronal damage in brain tissue caused by global cerebral ischemia/reperfusion (I/R) in C57BL/J6 mice. For this purpose, a total of 40 mice were divided equally into four groups: (1) sham-operated (SH), (2) global cerebral I/R, (3) HP, and (4) HP+I/R. The SH group was used as a control. In the I/R group, the bilateral carotid arteries were clipped for 15 min, and the mice were treated with vehicle for 10 days. In the HP group, mice were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 21 publications
1
21
0
1
Order By: Relevance
“…Inflammation and oxidative stress are associated with various life-threatening diseases including cancer (Oztanir et al, 2014), neurodegenerative diseases (Donato et al, 2014b;Hald and Lotharius, 2005) and cardiovascular diseases (Cottone et al, 2008). Oxidative stress can activate a variety of transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation and oxidative stress are associated with various life-threatening diseases including cancer (Oztanir et al, 2014), neurodegenerative diseases (Donato et al, 2014b;Hald and Lotharius, 2005) and cardiovascular diseases (Cottone et al, 2008). Oxidative stress can activate a variety of transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental transient cerebral ischemia, which is typically induced by middle cerebral artery occlusion in rats/mice, and bilateral common carotid artery occlusion in gerbils, has previously been associated with selective neuronal cell damage/death in vulnerable regions of the brain, including the neocortex and hippocampus ( 7 , 8 ). In addition, experimental transient cerebral ischemia-induced neuronal cell damage has been associated with free radical-associated damage and oxidative stress ( 7 , 9 , 10 ). Therefore, regulating oxidative stress levels and the production of antioxidants may be considered a potential strategy in the prevention and treatment of transient cerebral ischemia-induced neuronal cell damage/death ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…15 Through the I/R model, it has been found that by reducing oxidative stress neuronal damage in the brain could be prevented. 16 As neuronal apoptosis is an irreversible process, ameliorating oxidative stress could reduce the risk of neurodegenerative disease. A recent study showed the neuroprotective effects of β-myrcene, a natural product derived from thyme and parsley, in mice following I/R.…”
Section: Discussionmentioning
confidence: 99%